THE EFFECT OF FIVE WEEKS OF TRIBULUS TERRESTRIS SUPPLEMENTATION ON MUSCLE STRENGTH AND BODY COMPOSITION DURING PRESEASON TRAINING IN ELITE RUGBY LEAGUE PLAYERS - ROGERSON, SHANE; RICHES, CHRISTOPHER J.; JENNINGS, CARL; WEATHERBY, ROBERT P.; MEIR, RUDI A.; MARSHALL-GRADISNIK, SONYA M. (Journal of strength and conditioning research, 2007)
Tribulus terrestris is an herbal nutritional supplement that is promoted to produce large gains in strength and lean muscle mass in 5–28 days (15, 18). Although some manufacturers claim T. terrestris will not lead to a positive drug test, others have suggested that T. terrestris may increase the urinary testosterone/epitestosterone (T/E) ratio, which may place athletes at risk of a positive drug test. The purpose of the study was to determine the effect of T. terrestris on strength, fat free mass, and the urinary T/E ratio during 5 weeks of preseason training in elite rugby league players. Twenty-two Australian elite male rugby league players (mean ± SD; age = 19.8 ± 2.9 years; weight = 88.0 ± 9.5 kg) were match-paired and randomly assigned in a double-blind manner to either a T. terrestris (n = 11) or placebo (n = 11) group. All subjects performed structured heavy resistance training as part of the clubʼs preseason preparations. A T. terrestris extract (450 mg·d) or placebo capsules were consumed once daily for 5 weeks. Muscular strength, body composition, and the urinary T/E ratio were monitored prior to and after supplementation. After 5 weeks of training, strength and fat free mass increased significantly without any between-group differences. No between-group differences were noted in the urinary T/E ratio. It was concluded that T. terrestris did not produce the large gains in strength or lean muscle mass that many manufacturers claim can be experienced within 5–28 days. Furthermore, T. terrestris did not alter the urinary T/E ratio and would not place an athlete at risk of testing positive based on the World Anti-Doping Agencyʼs urinary T/E ratio limit of 4:1.